Understanding foreign accent syndrome. Issue 11 (2nd March 2019) - McWhirter, Laura; Miller, Nick; Campbell, Catriona; Hoeritzauer, Ingrid; Lawton, Andrew; Carson, Alan; Stone, Jon
Abstract : Objective: Foreign accent syndrome (FAS) is widely understood as an unusual consequence of structural neurological damage, but may sometimes represent a functional neurological disorder. This observational study aimed to assess the prevalence and utility of positive features of functional FAS in a large group of individuals reporting FAS. Methods: Participants self-reporting FAS recruited from informal unmoderated online support forums and via professional networks completed an online survey. Speech samples were analysed in a subgroup. Results: Forty-nine respondents (24 UK, 23 North America, 2 Australia) reported FAS of mean duration 3 years (range 2 months to 18 years). Common triggers were: migraine/severe headache (15), stroke (12), surgery or injury to mouth or face (6) and seizure (5, including 3 non-epileptic). High levels of comorbidity included migraine (33), irritable bowel syndrome (17), functional neurological disorder (12) and chronic pain (12). Five reported structural lesions on imaging. Author consensus on aetiology divided into, 'probably functional (n=35.71%), 'possibly structural' (n=4.8%) and 'probably structural' (n=10.20%), but positive features of functional FAS were present in all groups. Blinded analysis of speech recordings supplied by 13 respondents correctly categorised 11 (85%) on the basis of probable aetiology (functional vs structural) in agreement with case history assignment. Conclusions: This largest case series to date details the experience of individuals with self-reported FAS. Although conclusions are limited by the recruitment methods, high levels of functional disorder comorbidity, symptom variability and additional linguistic and behavioural features suggest that chronic FAS may in some cases represent a functional neurological disorder, even when a structural lesion is present.